ANALISIS KINERJA KEUANGAN KOPERASI SEMOGA SEJAHTERA DI DESA SULIGI KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Mariana, Dina; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Semoga Sejahtera Cooperation have been roled in improving the economy and welfare of the members in various of business activities. The used of management cooperation is essential for the development and efficiency of cooperative efforts. The success of Semoga Sejahtera Cooperation is closely related to its performance. The performance appraisal of Semoga Sejahtera Cooperation is very important to describe how cooperatives the cooperation to run their business. In analyzing the performance of Semoga Sejahtera Cooperation with financial ratio analysis such as: the liquidity, solvency, profitability and activity as well as economic value added analysis is aimed to analyze the development of the cooperative financially over the last five years. This study uses a case study method with the object of research is Semoga Sejahtera Cooperation. The data required in this research consisted of primary data and secondary data. The result shows that the Semoga Sejahtera Cooperation has good financial performance during the last five years from 2009 to 2013. This can be seen from the analysis of financial ratios include liquidity ratio that can still be maintained in a liquid state, cooperative debt decreased, the ability of cooperatives to generate profits, the ratio aktivatas and positive economic value added. Keywords : financial performance, financial ratio, economic value added